2022
DOI: 10.1161/strokeaha.120.034029
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Caregiver Preparedness on the Relationship Between Depression and Quality of Life in Stroke Dyads

Abstract: Background and Purpose: Depression and quality of life (QOL) have an interdependent and transactional nature in stroke survivor-caregiver dyads. While the strong relationship between depression and physical and emotional QOL in stroke survivor-caregiver dyads is well known, it is less clear if this relationship is moderated by caregiver preparedness, which could easily be targeted with interventions. In this study, we examined the moderating role of caregiver preparedness on the association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
(65 reference statements)
1
8
0
Order By: Relevance
“…The results of this study also have identified that informal caregivers' preparedness can provide a significant benefit to HF patients' quality of life. Our finding was similar to those of Pucciarelli et al 52 and Magasi et al, 19 who found that informal caregivers' preparedness had a positive influence on the quality of life of stroke survivors and patients with mechanical circulatory support. In China, most patients with HF will recover at home.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study also have identified that informal caregivers' preparedness can provide a significant benefit to HF patients' quality of life. Our finding was similar to those of Pucciarelli et al 52 and Magasi et al, 19 who found that informal caregivers' preparedness had a positive influence on the quality of life of stroke survivors and patients with mechanical circulatory support. In China, most patients with HF will recover at home.…”
Section: Discussionsupporting
confidence: 92%
“…These data suggest that healthcare professionals should provide individualized guidance to informal caregivers to prepare them to deal with patient emergencies. Previous investigators have shown that caregiver preparedness had a positive impact on caregivers' outcomes, [49][50][51] but few researchers have examined the influence of caregiver preparedness on patients' outcomes, 52 and no research has been conducted in the HF population with insufficient self-care. To our knowledge, ours is the first study to observe the impact of informal caregivers' preparedness on patients' psychological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies ( 11 , 16 ), depressive symptoms are associated with the severity of functional disability of the patients as they are more likely to rely on caregivers for support and care ( 56 ). Meanwhile, caregivers with a higher education level tend to experience fewer depressive symptoms, which may be attributed to better ways to insight into illness and seek help ( 57 ). The study has shown that unemployment and low income are risk factors for depressive symptoms as limited economic resources, substantial uncertainty and income volatility expose them to physical and mental stress ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…142 Caregivers who have better caregiver preparedness are less likely to suffer from mood disturbances, experience lower burden of care, and perform better selfcare. 142 Chronically critically ill young patients whose family members are younger may experience a lower health-related quality of life. 143,144 This could be related to greater emotional interdependence to one another among younger patient-caregiver dyads, occupational disability, financial burdens, and caring for young children in addition to taking over informal caregiving tasks and assistance in ADL.…”
Section: Family and Caregiver Picsmentioning
confidence: 99%